2019
DOI: 10.1111/jop.12847
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of pemphigus vulgaris: A retrospective consideration of 98 patients treated in an oral medicine unit in north‐west Italy

Abstract: Background Despite the frequency of oral involvement, there are unexpectedly few studies of either on the oral manifestations of pemphigus or their long‐term management, and diagnostic delay in Dentistry is frequent. Methods We have examined outcome of patients presenting with predominantly oral pemphigus vulgaris (PV). Ninety‐eight subjects were followed up for 85.12 months and treated with systemic steroids: 48 of them received adjunctive therapy with azathioprine, 16 with rituximab, 13 with mycophenolate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 31 publications
4
36
1
Order By: Relevance
“…Pemphigus vulgaris (PV) usually affects first the oral mucosa, and its management aims to induce and maintain clinical remission with as few as possible adverse effects. Because of the lack of international agreed recommendations, both the dosage of corticosteroids and choice of adjuvant agents usually reflect the experience of clinicians at various centers . Recently, we confirmed that systemic corticosteroid should be considered the mainstay medication for predominantly oral involvement …”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…Pemphigus vulgaris (PV) usually affects first the oral mucosa, and its management aims to induce and maintain clinical remission with as few as possible adverse effects. Because of the lack of international agreed recommendations, both the dosage of corticosteroids and choice of adjuvant agents usually reflect the experience of clinicians at various centers . Recently, we confirmed that systemic corticosteroid should be considered the mainstay medication for predominantly oral involvement …”
Section: Introductionmentioning
confidence: 61%
“…The control group comprised 95 unrelated Caucasian patients (60 female and 35 male), together with two female and one Afro‐Caribbean male (F: M; 1.65:1), mean age 54.56 (±14.95) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations